No association between genetic or epigenetic variation in insulin growth factors and antipsychotic-induced metabolic disturbances in a cross-sectional sample. (May 2014) - Moons, Tim; Hert, Marc De; Kenis, Gunther; Viechtbauer, Wolfgang; Os, Jim van; Gohlke, Henning; Claes, Stephan; Winkel, Ruud van
Aim: Second-generation antipsychotics (SGA) are known to induce metabolic disturbances. Genetic pathways, such as the IGF pathway could be associated with increased metabolic syndrome (MetS). Additionally, IGF2 methylation varies as a function of environmental influences and is associated with schizophrenia and MetS. The current study aims to evaluate whether genetic and epigenetic variation in genes of the IGF pathway are associated with metabolic disturbances in patients under treatment with SGAs.Methods: Cross-sectional metabolic data from 438 patients with schizophrenia spectrum disorder was analyzed. Using the Sequenom MassARRAY iPLEX TM platform, 27 SNPs of the IGF1 and IGF2 genes and the IGF receptors IGF1R and IGF2R were genotyped . Methylation status of seven IGF2 CpG dinucleotides was evaluated using a Sequenom MALDI-TOF spectrometer.Results & conclusion: There was a significant association between IGF2 methylation and genotype, but no significant association between genetic or epigenetic variability and metabolic parameters in the present study. Original submitted 28 October 2013; Revision submitted 7 March 2014